The Development of PBL-Based Worksheets Integrated with Green Chemistry and Ethnoscience to Improve Students’ Thinking Skills - Sudarmin, S.; Zahro, L.; Pujiastuti, S. E.; Asyhar, R.; Zaenuri, Z.; Rosita, A. (Jurnal Pendidikan IPA Indonesia, 2019)
In todayÃ¢â‚¬â„¢s global era, thinking skills are essential to be mastered by students. This research intended to develop and implement PBL-based worksheets integrated with green chemistry and ethnoscience to improve thinking skills, which included generic science skills and critical thinking skills. These skills were observed through learning outcomes, which were divided into three domains, i.e., cognitive, psychomotor, and affective. The cognitive aspect was assessed through pre- and post-test results, the psychomotor domain was valued through an essay test and observational sheets, and the affective domain was evaluated using questionnaires and observational sheets. This research was conducted with XI graders of MAN I Semarang and SMA Pekalongan. There were three rounds implemented; first, preliminary research which has observed the problems in chemistry learning, particularly on the hydrolysis topic and continued to the development of worksheets, then validated. The next round was the implementation of the worksheets. The N-gain test was used to see the influence of the developed worksheets on the increase in critical thinking skills and generic science skills. The critical thinking scored 0.58 (moderate), while the generic science, which covered scale awareness and logical inference, scored 0.63 (moderate) and 0.73 (high), respectively. A paired t-test results revealed that there was a remarkable increase in the logical inference and awareness of scale. Moreover, the results of the study found that the applied worksheets were practical for cognitive, affective, psychomotor seen from the learning outcomes.Ã‚Â